Assessment of Osteobrama belangeri (Pengba), a high-value medium carp endemic to North-east India for thermal tolerance limits - Sanjay Kumar Das; Sevok Handique; Debnath, Chandan; S. Gojendra Singh; Prasanta Mahanta (Indian Journal of Fisheries, 2023)
Critical thermal maxima (CTmax), lethal temperature maxima (LTmax), opercular respiration rate (ORR - movement of operculum per minute), temperature quotient (Q10) and stress markers of Osteobrama belangeri (Pengba), a high-value medium carp endemic to hilly ecosystems of North-east India, were examined with the aim of understanding its aquaculture potential and management requirements in the event of a temperature rise. Fish (7.82±0.35 cm/4.64±0.36 g) were acclimatised at 20, 25 and 30°C in insulated tanks (10 fish per tank) for 30 days. They were then exposed to a water temperature increase (@ 1°C day-1) using a locally-fabricated thermostat and assessed for CTmax, LTmax and ORR. As the acclimation temperature increased from 20 to 30°C, CTmax, LTmax and ORR of the fish significantly increased. Regression analysis indicated a strong positive correlation between acclimation temperatures and CTmax (y = 0.22x + 33.55, R² = 0.97) and LTmax (y = 0.27x + 32.86, R² = 0.99). Fish blood samples were collected at the endpoints of CTmax and LTmax and analysed for serum alkaline phosphatase (ALP) activity. The results indicated that the fish experienced maximum stress at an acclimation temperature of 30°C (ALP: 38.7 U l-1), followed by 25°C (35.6 U l-1) and 20°C (31.7 U l-1). The results suggested that a water temperature increase above 30°C can impair the physiology of O. belangeri and consequently, their reproductive competence. Therefore, in such events, proper management and additional care are necessary to protect them from extinction. Keywords: Critical thermal maxima, Lethal temperature maxima, Osteobrama belangeri, Thermal limit, Temperature quotient